2009
DOI: 10.1007/s00122-009-1100-8
|View full text |Cite
|
Sign up to set email alerts
|

The potato R locus codes for dihydroflavonol 4-reductase

Abstract: The potato R locus is required for the production of red pelargonidin-based anthocyanin pigments in potato (Solanum tuberosum L.). Red color also requires tissue-speciWc regulatory genes, such as D (for expression in tuber skin) and F (expression in Xowers). A related locus, P, is required for production of blue/purple anthocyanins; P is epistatic to R. We have previously reported that the dihydroXavonol 4-reductase gene (dfr) co-segregates with R. To test directly whether R corresponds to dfr, we placed the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 27 publications
1
47
0
1
Order By: Relevance
“…In the study of Zhang et al, the dihydroflavonol 4-reductase gene (dfr) was introduced into the potato cultivar Prince Hairy (white tuber) under the control of a double CaMV 35S promoter, resulting in a change in the color of the flowers of the transgenic plant from light blue to purple, but no change in tuber color (Zhang et al 2009). As shown in our results, under the mediation of the GBSSI promoter, only the color of the tubers deepened.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Zhang et al, the dihydroflavonol 4-reductase gene (dfr) was introduced into the potato cultivar Prince Hairy (white tuber) under the control of a double CaMV 35S promoter, resulting in a change in the color of the flowers of the transgenic plant from light blue to purple, but no change in tuber color (Zhang et al 2009). As shown in our results, under the mediation of the GBSSI promoter, only the color of the tubers deepened.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the QTL we have detected is indeed the R locus. This hypothesis could be easily confi rmed because the gene for R, a dihydrofl avonol 4-reductase, has recently been cloned (Zhang et al, 2009). A QTL for pigmented fl owers was also located on chromosome II of B1829-5, but at a diff erent position (58 vs. 8 cM).…”
Section: Qtl-corroborations and New Findingsmentioning
confidence: 97%
“…Where genetic and biochemical information is available on metabolic pathways, such as those for carbohydrates, anthocyanins, and carotenoids in potatoes, candidate genes are being postulated and sought for improving both qualitative and quantitative traits. For example, Zhang et al (2009) have confirmed that the potato R locus codes for dihydroflavonol 4-reductase and that a specific allele of the dfr gene is required for the production of red pelargonidin-based anthocyanin pigments. Furthermore, advances in metabolite profiling are allowing a systems approach to understanding biochemical pathways and hence the key genes to target for desired phenotypic (trait) changes.…”
Section: Gene Discovery (Linkage Maps Sequencing and Microarrays)mentioning
confidence: 89%